민사책임에 대한 타자철학적 기초 놓기 -민사법, 직근성(proximity), 책임 - 이영록(Lee, Young-Lok) (Pŏpch'ŏrhak yŏn'gu, 2019)
이 글의 일차적인 목적은 불법행위책임을 중심으로 하여 민사책임의 의미와 이념을 통일적으로 이해할 수 있는 철학적 기초를 제공하는 것이다. 이 글에서는 이를 레비나스(Emmanuel Levinas)의 타자철학의 핵심에 해당하는 직근성(proximity) 개념의 도움을 받아 시도한다. 이를 바탕으로 민사책임의 의미를 책임 일반이론과 연계해 보는 것이 이 글의 이차적 목적이다. 달리 말하면, 민사법의 이념, 책임의 일반이론, 타자법철학의 교집합에 해당하는 이론을 구성해보는 것이 이 글이 전체적으로 의도하는 것이다. 이를 위해 먼저 기존의 법경제학적 입장과 교정적 정의의 관점을 검토하고, 대안적 이론을 제시한다. 민사책임의 이념은 특정인에게 발생한 불행과 관련하여 직접적 연대의 실현으로, 민사 영역에서의 책임(responsibility)의 의미는 ‘직접적 연대를 요구받고 있음’, 혹은 ‘그 요구에 응답함’으로 이해할 수 있다는 것이다. 또한 책임의 한 내용으로서 피고가 지는 부담은 그런 요구가 전달됐음을 확증하는 방식으로 요구를 전달하는 일종의 의사소통으로 보아야 한다는 것이 이 글의 제안이다. 결론에서는 이런 민사책임에 대한 이해가 책임의 일반이론과의 관계에서 어떤 의미를 가지는지를 언급하는 것으로 마치고자 한다. The primary purpose of this article is to provide a philosophical basis for coherently understanding the meaning of, and justifying civil responsibility focused on torts. It is attempted by an application of the concept of proximity that is at the heart of Emmanuel Levinas' philosophy of the Other. The second purpose of this article is to link the meaning of civil responsibility with the general theory of responsibility. In other words, I intend to construct a theory that corresponds to the intersection of the philosophical foundation of private law, the general theory of responsibility, and legal philosophy of the Other. To this end, I first examine the two powerful theories of Law & Economics and corrective justice, then propose the alternative theory as follows. The inherent purpose of civil responsibility should be understood as the realization of direct solidarity between two parties with regard to the misfortunes experienced by a person, and the meaning of responsibility in the private law as 'being urged of direct solidarity' or 'responding to the urge'. The burden or disadvantage of the defendant inflicted as a result of responsibility should be viewed as a kind of communication that conveys the urge in a way that confirms that the urge has been delivered. At the last part, I refer to the implications of this understanding of civil responsibility in relation to the general theory of responsibility. KCI Citation Count: 0